Orexinergic System in Neurodegenerative Diseases - Wang, Qinqin; Cao, Fei; Wu, Yili (Frontiers in Aging Neuroscience, 2021)
Orexinergic system consisting of orexins and orexin receptors plays an essential role in regulating sleep-wake states, while sleep disruption is a common symptom of a number of neurodegenerative diseases. Emerging evidence reveals that orexinergic system is disturbed in various neurodegenerative diseases including Alzheimer's disease (AD), Parkinson’s disease (PD), Huntington's disease (HD) and Multiple sclerosis (MS), while the dysregulation of orexins and/or orexin receptors contributes to the pathogenesis of these diseases. In this review, we summarized advanced knowledge of orexinergic system and its role in sleep, and reviewed the dysregulation of orexinergic system and its role in the pathogenesis of AD, PD, HD and MS. Moreover, the therapeutic potential of targeting orexinergic system for the treatment of these diseases was discussed.